Digital Archaeological Data in the Wild West: the challenge of practising responsible digital data archiving and access in the United States - Christopher Nicholson; Rachel Fernandez; Jessica Irwin (Internet Archaeology, 2021)
Archaeology in the United States is conducted by a number of different sorts of entities under a variety of legal mandates that lack uniform standards for data archiving. The difficulty of accessing data from projects in which one was not directly involved indicates an apparent reluctance to archive raw data and supplemental information with digital repositories to be reused in the future. There is hope that additional legislation, guidelines from professional organisations, and educational efforts will change these practices.